2010
DOI: 10.1038/ncb2058
|View full text |Cite
|
Sign up to set email alerts
|

The role of Cdk5-mediated apurinic/apyrimidinic endonuclease 1 phosphorylation in neuronal death

Abstract: Accumulating evidence suggests that deregulated cyclin-dependent kinase 5 (Cdk5) plays a critical part in neuronal death. However, the pathogenic targets of Cdk5 are not fully defined. Here we demonstrate that the Cdk5 activator p35 interacts directly with apurinic/apyrimidinic endonuclease 1 (Ape1), a protein crucial for base excision repair (BER) following DNA damage. Cdk5 complexes phosphorylate Ape1 at Thr 232 and thereby reduces its apurinic/apyrimidinic (AP) endonuclease activity. Ape1 phosphorylation is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
112
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(114 citation statements)
references
References 51 publications
0
112
2
Order By: Relevance
“…For siRNA transfection, neurons were transfected with 30 pmol/well (24-well plate) siRNA to mouse bag2, pink1, or parkin plus 30 pmol/well of control siRNA to 60 pmol siRNA in total. For co-transfection of siRNAs, neurons were transfected with 30 pmol/well of each using Lipofectamine 2000 as described previously (32). 24 h after transfection, the neurons were treated with 20 M MPP ϩ for 48 h. The 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay was carried out.…”
Section: Methodsmentioning
confidence: 99%
“…For siRNA transfection, neurons were transfected with 30 pmol/well (24-well plate) siRNA to mouse bag2, pink1, or parkin plus 30 pmol/well of control siRNA to 60 pmol siRNA in total. For co-transfection of siRNAs, neurons were transfected with 30 pmol/well of each using Lipofectamine 2000 as described previously (32). 24 h after transfection, the neurons were treated with 20 M MPP ϩ for 48 h. The 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay was carried out.…”
Section: Methodsmentioning
confidence: 99%
“…With regard to PD, one recent study involving 60 case subjects and 108 normal controls found that the D148E variant of APE1 had a positive association as a risk factor for the disease (59), although it was acknowledged by the authors that more extensive follow-up experiments are needed to validate this observation. Finally, Huang et al (84), in addition to confirming the importance of APE1 in neuronal cell viability, possibly in a mechanism involving Cdk5 phosphorylation of residue T232 (in the mouse protein, T233 in the human protein), which inactivates the enzyme's AP endonuclease activity (see Table 1), detected an increase in the T233-phosphorylated form of APE1 in post-mortem brain samples from PD and AD patients, uncovering a possible molecular connection between APE1 inactivation and neurodegenerative disease.…”
Section: Neuropathologymentioning
confidence: 99%
“…[10][11][12] Activation of CDK5 requires its regulatory partner CDK5R1/p35/p25 (cyclin-dependent kinase 5, regulatory subunit 1 [p35]). 13 Accumulating evidence indicates that MPTP increases CDK5 activity 11,12 and triggers neuronal loss through phosphorylation and inhibition of PEBP1/RKIP (phosphatidylethanolamine-binding protein 1), 14 survival factor MEF2 (myocyte enhancer factor 2), 15 antioxidant enzyme PRDX2/Prx2 (peroxiredoxin 2), 16 and APEX1/Ape-1 (APEX nuclease [multifunctional DNA repair enzyme] 1). 11 Autophagy is a lysosomal degradation pathway that controls the turnover of cytoplasmic contents and organelles through the engulfment of cargo into double-membrane autophagosomes.…”
Section: Introductionmentioning
confidence: 99%